Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T19:26:59+01:00
13e - 5(f-3e)=13e - 5f+15e = 2e - 5f
4(-2r+s) - 10,5r= -8r + 4s - 10,5 r = -18,5r + 4s
-3(3x-2y)+2(x-2y)= -9x + 6y + 2x - 4y = -7x + 2y
-5(2z-3y)-4(4z-2y)= -10z + 15y - 16z +8y = -26z + 23y
2(2p-3q+7)-3(p-2q+4)= 4p - 6q + 14 - 3p + 6q - 12 = p + 14
2(3x²-2y+5y²)-3(4y+5y²)+2x-3x²= 6x² - 4y +10y² - 12y + 15y² + 2x - 3x²= 9x² - 16y + 25y² + 2x
2009-12-07T19:29:29+01:00
13e - 5(f-3e)=13e-5f-15e = -2e-5f

4(-2r+s) - 10,5r = -8r+4s-10.5r = -18,5r+4s


-3(3x-2y)+2(x-2y)=-9x+6y+2x-4y = 11x+2y

-5(2z-3y)-4(4z-2y)=-10z+15y-16z+8y = -26z+23y

2(2p-3q+7)-3(p-2q+4)=4p-6q+14-3p+6q-12 = p-2

2(3x²-2y+5y²)-3(4y+5y²)+2x-3x²=6x²-4y+10y²-12y-15y²+2x-3x²=3x²-16y-5y²+2x
  • egdl
  • Rozwiązujący
2009-12-07T19:30:15+01:00
13e-5(f-3e)= 13e -5f+15e=28e-5f
4(-2r+s)-10,5r= -8r+4s-10,5r=-18r+4s
-3(3x-2y)+2(x-2y)=-9x+6y+2x-4y=-7x+2y
-5(2z-3y)-4(4z-2y)= -10z+15y-16z+8y=-26z+24y
2(2p-3q+7)-3(p-2q+4)=4p-6q+14-3p+6q-12=p+2
2(3xkwadrat-2y+5ykwadrat)-3(4y+5ykwadrat)+2x-3xkwadrat=
6xkwadrat-4y+10ykwadrat-12y-15ykwadrat+2x-3xkwadrat=3xkwadrat-16y-5ykwadrat+2x